INTELLECTUAL CAPITAL AND BUSINESS PERFORMANCE (STUDY IN SASIRANGAN SME) - Muhammad Ziyad; Maya Sari Dewi; Redawati (Universitas Lambung Mangkurat, 2020)
This study aims to research aimed at analyzing the effect of Intellectual Capital on the business performance of Sasirangan UKM in Banjarmasin City. TheElement Intellectual Capitalin this study consists of Human Capital, Structural Capital, and Customer Capital contained in a business company. This research is a type of causal research that aims to get evidence about causal relationships (causal relationships) and is carried out using a quantitative approach. The population in this study were all UKM sasirangan in Banjarmasin City. according to Roscoe (1975) in Uma Sekaran (2006) In general, for correlational research the minimum number of samples to obtain good results is between 30 to So the number of samples used in this study is as many as 40 Sasirangan SMEs in Banjarmasin . Sampling based on purposive sampling with the criteria of UKM Sasirangan who are older than 1 year. The results showed that, Human Capital and Structural Capital had a positive effect on the performance of Sasirangan UKM in Banjarmasin while Customer Capital had no effect on Sasirangan UKM.